Tradisi Omed-Omedan Banjar Kaja Kelurahan Sesetan Keca- Matan Denpasar Selatan - Ni Luh Ketut Sukarniti (Jurnal Ilmiah Cakrawarti, 2020)
Balinese always preserve cultural traditions as the inheritance of their ancestors. Omed-omedan tradition is a unique and rare tradition since such tradition cannot be encountered in  other areas. Therefore, it  is  interesting to  be  discussed in a paper. This reseacrh was aimed at finding out: How is the process of implementa- tion of Omed-omedan tradition at Banjar Kaja Kelurahan Sesetan, South Denpasar Sub-District, Denpasar City?, What is the relationship between Omed-omedan tradi- tion and the series of Nyepi Holiday at Banjar Kaja Kelurahan Sesetan, South Den- pasar Sub-District Denpasar City? What is the meaning of Omed-omedan tradition  for the people at Banjar Kaja Kelurahan Sesetan, South Denpasar Sub-District, Den- pasar City? The theoretical bases applied in this research are 1). Culture, 2). Reli- gious systems, 3). Society. The results of the research show that the implementation of Omed-omedan Tradition must be conducted as it relates to Ida Bhatara Sesuhunan at in Banjar Kaja Sesetan temple. Omedomedan tradition is also an event of Masima Krama (visit and forgive each other) to welcome Caka New Year (Nyepi Holiday). The conclusions of this research are 1). Omed-omedan tradition is Purwa Dresta, namely a religious custom and it is not allowed if it is not conducted because if it is not conducted, it is believed it would lead to the undesirable things, 2). In its perfor- mance, Omed-omedan tradition is an event of Masima Krama in order to welcome Caka New Year, 3). The meaning of this Omed-omedan tradition is as a devotion to Ida Bhatara Sesuhunan, as by always conducting this tradition, the members of Ban- jar Kaja Sesetan are believed to always have His protection.